2014
DOI: 10.1097/ta.0000000000000354
|View full text |Cite
|
Sign up to set email alerts
|

The whole is greater than the sum of its parts

Abstract: Although 1:1:1 RWB had a superior clotting profile relative to 2:1:1 RWB, MWB exhibited even better global hemostasis than did 1:1:1 RWB. Characterization of factor-level and functional clotting differences between WB variants is imperative for understanding the clinical benefits of hemostatic resuscitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 33 publications
1
27
0
Order By: Relevance
“…Further, PLT counts decreased significantly during storage in the studies of Jobes et al [21] and Pidcoke et al [22] without any correction of the results for this confounder. Further, Kornblith et al [24] compared fresh WB to expired PLT concentrates and Rodgers et al [23] only examined up till 3 days of storage, thereby making direct comparisons with the current study difficult.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Further, PLT counts decreased significantly during storage in the studies of Jobes et al [21] and Pidcoke et al [22] without any correction of the results for this confounder. Further, Kornblith et al [24] compared fresh WB to expired PLT concentrates and Rodgers et al [23] only examined up till 3 days of storage, thereby making direct comparisons with the current study difficult.…”
Section: Discussionmentioning
confidence: 85%
“…Nonetheless, the PLT aggregation capacity of WB is at least as good as it is in BCP or AP. Previous studies have shown reduced PLT aggregation capacity in BCP and AP during storage as measured by light transmission aggregometry [12][13][14][15][16][17][18] or multiple electrode aggregometry [12,13,19,20], but only few have compared PLT function in BCP or AP to that of WB [23,24]. Knowledge of PLT function in WB during storage is sparse and has shown conflicting results [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While our study reinforces WFWB as the gold-standard for hemorrhage resuscitation based on hemostatic properties, we have attempted to identify a product with comparable hemostatic properties that avoids the contemporary logistic and infectious concerns of WFWB [10,11]. Our study demonstrates that CWB holds great promise as a surrogate for WFWB, but that use of the platelet-sparing LR filter diminishes platelet function almost immediately after filtration (Table 1).…”
Section: Discussionmentioning
confidence: 97%
“…Haemostatic resuscitation is based on the administration of a mixture of red blood cells (RBCs), fresh frozen plasma (FFP) and platelets in approximately a 1:1:1 ratio. Such a strategy known as a 'balanced transfusion' would minimise the risk of dilution of coagulation factors leading to a reduction in the overall mortality rate in patients requiring massive transfusions [14].…”
mentioning
confidence: 99%